Growth and quality of mutant Axonopus compressus cultivars under different growing media - Yusuf, Munifah Siti Amira (2015)
Growing media is any organic or inorganic materials used for plants to grow. Different cultivars of turf grass species showed different responses towards different growing media. An experiment was conducted at the Unit Turf, UPM to evaluate the growth and quality of mutant Axonopus Compressus cultivars under different growing media. This study consist of one original cultivar of Axonopus compressus and four mutant cultivars of Axonopus compressus that were collected at Unit Turf Faculty of Agriculture UPM. The grasses were grown in plastic trays with the size of 37cm length X 27 cm width X 10 cm depth, containing four different growing media which were 100% sand (1 sand), 100% top soil (1 top soil), ratio of 3 top soil : 2 peat grow : 1 sand, and ratio of 8 sand : 2 peat grow. There were 80 trays (37cm x 27 cm x 10 cm) were used in this experiment and were arranged in factorial (5 cultivars x 4 media) experiment using Randomized Complete Block Design (RCBD) with four replications. Turf grass growth and quality were determined through several parameters that include growth rate cover, shoot and root dry and fresh weight, leaf length and width, internodes length, shoot density, turf grass color, root volume and root length. Starting from week 9 until week 12 of planting, the data of growth rate cover, leaf width, leaf length and shoot density were recorded weekly. The data of leaf colour, shoot fresh weight, shoot dry weight, root fresh weight, root dry weight, internodes length, root volume and root length were taken and recorded at the end of the 12 weeks experiment. The result showed that there were significant difference between media and cultivars. Different cultivars produced different growth and quality under different media. All the growing media produced and influenced good growth and quality for the cultivars. Treatment 2 (100% top soil) produced the best effect on growth and quality compared to other growing media for Axonopus compressus original (control), Mutant 4-A48, and Mutant A-13. Meanwhile, the best cultivars that adapt best on most of growing media are Axonopus compressus original (control) and Mutant 4-A48. This result suggests that different cultivars may show difference effect on different growing media of growth and quality of mutant Axonopus compressus cultivars.